Combination of Spirulina platensis powder and Stichopus variegatus powder against Bcl2 expression in the hippocampus of dementia Rats - Botutihe, Lisa Agustina; Safira, Rizka; Yuliani, Sapto; Kintoko, Kintoko (Pharmaciana, 2024)
Spirulina (Spirulina platensis) and golden sea cucumber (Stichopus variegatus) are known to have antioxidant activity that has the potential to prevent neurodegeneration disease. The aim of this study was to examine the effect of the combination of spirulina and golden sea cucumber on Bcl2 gene expression in pyramidal hippocampus cells of trimethyltin-induced dementia (TMT) rats. The study used Sprague Dawley rats  which were divided into 6 groups, namely the normal control group (CMC-Na and NaCl 0.9%), pain control (CMC-Na and TMT), positive control (citicoline dose 200 mg / kg and TMT) and test control injected with TMT and given a combination of spirulina and golden sea cucumber dose 200 mg/KgBB with three ratios namely 3: 1, 1: 1 and 1: 3. Extract and citicoline were given on day 1 to day 28, while TMT injection was given a single dose of 8 mg/KgBB on day 8. On the 36th day the rats were sacrificed, brains were removed and the right hemispherium cerebri was fed to 10% formalin in pbs. After 6 days the hippocampus was separated for immunohistochemical observation. The test result data was statistically analyzed with a one-way ANOVA test then followed by post hoc tukey to see the differences between groups. Results showed the combination of spirulina and golden sea cucumber can increase the expression of the Bcl2 gene in the hippocampus. The combination of spirulina and golden sea cucumber (ST1: 3) dose of 200 mg / kg body weight was able to increase hippocampus Bcl2 expression with the number of Bcl2 cell expression almost the same as citicoline in both CA1 and CA2-CA3 regions.